Integrated reporting vs. sustainability reporting for corporate responsibility in South Africa - Clayton, Alexandra F.; Rogerson, Jayne M.; Rampedi, Isaac (Bulletin of Geography. Socio-economic Series, 2015)
Large corporates have come under increasing pressure to conduct their business in a more transparent and responsible manner. In order for business to fulfil its obligations under the ethic of accountability stakeholders must be given relevant, timely, and understandable information about their activities through corporate reports. The conventional company reports on annual financial performance, sustainability and governance disclosures often fail to make the connection between the organisation’s strategy, its financial results and performance on environmental, social and governance issues. Recognising the inherent shortcomings of existing reporting models, there is a growing trend to move towards integrated reporting. South Africa has been one of the most innovative countries in terms of integrated corporate reporting. Since 2010 companies primarily listed on the country’s major stock exchange have been required to produce an integrated report as opposed to the former sustainability report. The aim in this study is to review the development of integrated reporting by large corporates in South Africa and assess the impact of the required transition from sustainability reporting to integrated reporting on non-financial disclosure of eight South African corporates using content analysis of annual reports.